The impact of viral marketing on consumers purchase decision in the Northern region / Mohd Najmie Osman, Muhammad Khairul Anwar and Hadzli Ishak - Osman, Mohd Najmie; Khairul Anwar, Muhammad; Ishak, Hadzli (Universiti Teknologi MARA, Perlis, 2018)
Viral marketing is a marketing technique whereby information about a company goods or services is passed electronically from one internet use to another. According some marketing scholar, viral marketing is the technique that replacing Worth of Mouth Marketing (WOMM) whereby marketer creates a campaign focused around the goal spontaneously spread it by sending it to friends by using social media such as Facebook and etc. The growth of online social networks around the world has created a new place of interaction and communication among people. Individuals can share their knowledge, opinions, and experiences with one other due to the online social networks provided features and may have an impact on people’s behavior in terms of communication and purchasing. The purpose of this study is to examine the impact of online social networks (Facebook) on consumers purchasing decision process. Technology Acceptance Model (TAM) undertaking as a framework for the investigation to support the findings. Perceive Usefulness and Perceive Ease of Use are use as independent variable and Consumer’s Purchase Decision represent as the dependent variable. The data will be statistically analyzed for reliability, correlation and multiple regression. The result would help the industry and future research area in finding the meaningful way to manage the complex issues regarding viral marketing issues in Malaysia.